Improved visible-blindness of AlGaN deep ultraviolet photodiode with monolithically integrated angle-insensitive Fabry–Perot filter - Kim, Dohyun; Han, Seungho; Jung, Joocheol; Baek, Yongmin; Son, John; Lee, Kyusang; Heo, Junseok (Optics Express, 2019)
Despite the rapidly increasing demand for accurate ultraviolet (UV) detection in various applications, conventional Si-based UV sensors are less accurate due to disruption by visible light. Recently, Ga(Al)N-based photodiodes have attracted great interest as viable platforms that can avoid such issues because their wide bandgap enables efficient detection of UV light and they are theoretically blind to visible and infrared light. However, the heteroepitaxy of a Ga(Al)N layer on sapphire substrates inevitably leads to defects, and the Ga(Al)N photodiode (PD) becomes not perfectly insensible to visible light. Employment of a dielectric stacked UV pass filter is possible to avoid unwanted absorption of visible light, but the angle-dependent pass band limits the detection angle. Here, we have demonstrated the Ag-Al2O3 Fabry–Perot UV pass filter-integrated AlGaN ultraviolet photodiode. The inherent optical extinction characteristics of Ag was utilized to design the fabrication-tolerant UV pass filter with a peak transmittance at ∼325 nm. As the angle of incidence increased, the peak transmission decreased from 45% to 10%, but the relative transmission spectrum remained almost unchanged. By integrating these filters, the visible light rejection ratio (responsivity for 315 nm light to responsivity for 405 nm light) was improved by a factor of 10, reaching a value of 106 at angles of up to 80 degrees.
Keywords: Deep-ultraviolet photodiodes; Efficient detection; Monolithically integrated; Optical extinction; Peak transmittance; Sapphire substrates; Transmission spectrums; Ultraviolet detection